A method for preparing a negative electrode material of a hard carbon-silicon dioxide composite lithium ion battery
Through the composite preparation method of biomass hard charcoal and silicon oxide, the lack of capacity and circulating performance of the existing lithium-ion batteries are solved. Composite lithium ion battery negative electrode material.
Patent Information
- Application Number
- CN202311172367.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-12
AI Technical Summary
The capacity of artificial graphite, anode material of existing lithium-ion batteries, is close to the limit, while pure silicon oxide has poor circulation and rate performance due to high volume expansion. The capacity of pure biomass hard carbon is low, which cannot meet the high energy density lithium. Requirements for ion batteries.
By compounding biomass hard charcoal and silicon oxide, specific preparation methods include mixed, heating carbonization, reaction, washing, drying, and ball milling, to prepare the negative electrode material of hard charcoal-oxidized subclase lithium-ion battery.
While realizing that the capacity is better than the artificial graphite, it maintains the cycle performance and multiplier performance of the artificial graphite, and solves the problem of the high volume expansion rate of the oxidation sub -oxide and the low biomass hard charcoal capacity.
Smart Images

Figure CN117199289B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a negative electrode material of a hard carbon-silicon dioxide composite lithium ion battery. Background Art
[0002] The power source of new energy vehicles is mainly lithium-ion batteries. Their rapid development and large-scale application have led to higher and higher requirements for the energy density (measurement of the driving range after a single full charge) and charging speed of lithium-ion batteries. As an important component of lithium-ion batteries, the gram capacity, cycle performance and rate performance of the negative electrode have a significant impact on the energy density and charging speed of lithium-ion batteries. At present, the negative electrode of commercial lithium-ion batteries is mainly based on artificial graphite. The theoretical gram capacity of artificial graphite is only 372mAh / g, while the gram capacity of the current high-end artificial graphite negative electrode has reached more than 360mAh / g, which is close to the theoretical gram capacity. Therefore, it is no longer feasible to use artificial graphite negative electrodes to prepare high-energy-density lithium-ion batteries. Silicon, which is in the same main group as the constituent element carbon of graphite, has similar properties to carbon, so its monovalent oxide-silicon dioxide can also be used as a negative electrode material for lithium-ion batteries, and its theoretical gram capacity is 1800mAh / g, which is more than 5 times that of artificial graphite. Therefore, it is regarded as a revolutionary alternative material for high-energy-density lithium-ion battery negative electrodes. However, pure silicon oxide as a negative electrode material for lithium-ion batteries will produce a 180 / 100 volume expansion during the charge and discharge process of lithium ion insertion and extraction, resulting in the destruction and failure of the negative electrode structure and causing defects such as poor cycle performance and poor rate performance. It can only be used as a negative electrode for lithium-ion batteries after reducing the volume expansion rate through technical modifications (such as coating, composite, etc.).
[0003] Different from the crystal structure of artificial graphite, which is arranged in an orderly manner at the microscopic level, the microstructure of biomass hard carbon is arranged in a disordered and chaotic amorphous structure. Such a microstructure allows lithium ions to have more diffusion channels and less diffusion resistance, resulting in excellent rate performance and cycle performance. However, the amorphous structure of biomass hard carbon results in limited positions for accepting lithium ions, so its gram capacity is low and is not suitable for use in high energy density fields. Therefore, the present invention compounds biomass hard carbon and silicon dioxide through certain technical means, which can not only solve the technical defects of poor cycle performance, poor rate performance and low gram capacity of silicon dioxide and biomass hard carbon, but also can prepare a lithium ion battery negative electrode material with a gram capacity superior to that of artificial graphite and comparable cycle performance and rate performance. Summary of the invention
[0004] In order to solve the technical defects that the gram capacity, cycle performance and rate performance of existing artificial graphite negative electrode of lithium ion battery are close to the limit, and if pure silicon oxide is used as negative electrode to improve the gram capacity, its volume expansion rate is large and the cycle and rate performance are poor, and if pure biomass hard carbon is used to improve the cycle and rate performance, its gram capacity is low and it cannot be used in high energy density lithium ion batteries, the purpose of the present invention is to provide a method for preparing hard carbon-silicon oxide composite lithium ion battery negative electrode material, which can prepare a hard carbon-silicon oxide composite lithium ion battery negative electrode material with better gram capacity than artificial graphite and comparable cycle performance and rate performance.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a hard carbon-silicon dioxide composite lithium ion battery negative electrode material, comprising the following steps:
[0006] (1) mixing the silicate-containing biomass and the alkali metal compound uniformly and then heating and carbonizing them to obtain a biomass hard carbon-sodium silicate mixture;
[0007] (2) adding aqua regia to the biomass hard carbon-sodium silicate mixture obtained in step (1) to react, dissolving the metal compound impurities in the biomass hard carbon into metal ions and converting the sodium silicate into silicic acid to obtain a hard carbon-silicic acid sol mixture;
[0008] (3) washing and drying the hard carbon-silicic acid sol mixture obtained in step (2) to obtain a hard carbon-silicic acid solid mixture;
[0009] (4) The hard carbon-silicic acid solid mixture obtained in step (3) is heated and then ball-milled to obtain a hard carbon-silicon dioxide composite lithium-ion battery negative electrode material.
[0010] Optionally, the silicate-containing biomass in step (1) is one of walnut shell and peanut shell biomass.
[0011] Optionally, the alkali metal compound in step (1) is one or a mixture of two of sodium hydroxide, sodium carbonate and sodium borate.
[0012] Optionally, the mass ratio of the biomass to the alkali metal compound in step (1) is 100:10-40.
[0013] Optionally, the equipment used for mixing the biomass and the alkali metal compound in step (1) is a cone mixer, the mixer speed is 300-500 r / min, and the mixing time is 1-4 hours.
[0014] Optionally, the heating carbonization in step (1) is carried out in a tubular furnace with a protective atmosphere, the carbonization temperature is 800-1200°C, the carbonization time is 2-4 hours, the heating rate is 2-10°C / minute, the protective atmosphere is nitrogen, and the nitrogen flow rate is 100-200mL / min.
[0015] Optionally, the mass ratio of aqua regia to the biomass hard carbon-sodium silicate mixture in step (2) is 16-25:1.
[0016] Optionally, the reaction of aqua regia and the biomass hard carbon-sodium silicate mixture in step (2) is carried out on a magnetic heating stirrer, with a heating temperature of 200-300° C., a reaction time of 4-8 hours, and a stirring speed of 600-1200 r / min.
[0017] Optionally, the washing process in step (3) is as follows: first, the reaction product in step (2) is allowed to stand and settle for 10-15 minutes, the supernatant is poured out and 1L of high-purity deionized water is added, the mixture is stirred for 1 minute, and then allowed to stand and settle for another 10-15 minutes, and this washing is repeated 5-10 times until the pH of the reaction product reaches between 6.5 and 7 and the washing is completed.
[0018] Optionally, the drying in step (3) is carried out in a vacuum drying oven, the vacuum pressure is less than 100 Pa, the drying temperature is 80-120° C., and the drying time is 4-8 hours.
[0019] Optionally, the heating reaction in step (4) is carried out in a box-type resistance furnace, with a heating temperature of 400-600° C., a heating time of 2-4 hours, and a heating rate of 4-8° C. / min.
[0020] Optionally, the ball milling in step (4) is carried out in a vacuum planetary ball mill with a vacuum degree of less than 100 Pa, a ball milling speed of 400-800 r / min, and a ball milling time of 6-12 hours.
[0021] Correspondingly, the present invention also claims protection for a hard carbon-silicon dioxide composite lithium ion battery negative electrode material prepared by the aforementioned preparation method.
[0022] Correspondingly, the present invention also claims to protect the use of the hard carbon-silicon dioxide composite lithium ion battery negative electrode material obtained by the aforementioned preparation method in the preparation of lithium ion batteries.
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial effects and innovations:
[0024] 1. Biomass is used as the raw material for preparing the negative electrode of lithium-ion batteries, which has a wide source and low cost.
[0025] 2. The silicon oxide in the hard carbon-silicon oxide composite lithium-ion battery negative electrode material comes from the silicate ash in the hard carbon itself. It is essentially an impurity for hard carbon. Before the hard carbon negative electrode is used in lithium-ion batteries, it needs to be purified and removed by certain technical means. This solution converts it into silicon oxide and hard carbon together, which not only has the effect of purification and removal, but also can improve the gram capacity of the composite negative electrode material.
[0026] 3. After high-temperature heating and carbonization, a large number of small molecular volatiles are discharged from biomass hard carbon, resulting in a large number of pores. A rich pore structure is formed at the microscopic level. These pores can accommodate silicon oxide molecules, reduce the volume expansion rate of silicon oxide during the charge and discharge process of lithium-ion batteries, or buffer the stress generated by volume expansion, and ultimately allow silicon oxide to maintain a stable structure, thereby preventing defects such as shortened cycle life and poor rate performance due to structural failure.
[0027] 4. Before ball milling, the ball mill should be evacuated to exhaust the air in the pores of the hard carbon and put it in a vacuum state. In this way, during the ball milling process, silicon dioxide will enter the pores of the hard carbon more easily due to the pressure difference between the inside and the outside. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1-2 The relationship diagrams of charge gram capacity and cycle number after the negative electrode materials of Examples 1-2 are prepared into button-type batteries. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described below through specific embodiments.
[0030] Example 1
[0031] A method for preparing a hard carbon-silicon dioxide composite lithium ion battery negative electrode material comprises the following steps:
[0032] (1) 500 g of walnut shell biomass and a mixture of 125 g of sodium carbonate and sodium borate were uniformly mixed in a conical mixer, the mass ratio of sodium carbonate to sodium borate was 7:3, the mixer speed was 400 r / min, and the mixing time was 1.5 hours;
[0033] (2) 200 g of the mixed product obtained in step (1) was heated and carbonized in a tube furnace at a carbonization temperature of 900° C. for 3 hours at a heating rate of 3° C. / min. The protective atmosphere was nitrogen at a nitrogen flow rate of 150 mL / min. After carbonization, a biomass hard carbon-sodium silicate mixture was obtained;
[0034] (3) 100 g of the biomass hard carbon-sodium silicate mixture obtained in step (2) was placed in a beaker, 1800 ml of aqua regia was added, and the mixture was placed on a magnetic heating stirrer for reaction for 4 hours at a heating temperature of 250° C. and a stirring speed of 800 r / min to obtain a hard carbon-silicic acid sol mixture;
[0035] (4) The hard carbon-silicic acid sol mixture obtained in step (3) was allowed to stand for 10 minutes, the supernatant was poured out and 1 L of high-purity deionized water was added, and the mixture was stirred with a glass rod for 1 minute, and then allowed to stand for another 10 minutes. After repeating the washing for 6 times, the pH of the reaction product was 6.8, and the washing was stopped to obtain a hard carbon-silicic acid sol mixture slurry;
[0036] (5) placing the hard carbon-silicic acid sol mixture slurry obtained in step (4) in a vacuum drying oven for drying, the vacuum pressure is 90 Pa, the drying temperature is 100° C., and the drying time is 6 hours to obtain a hard carbon-silicic acid solid mixture;
[0037] (6) heating the hard carbon-silicic acid solid mixture obtained in step (5) in a box-type resistance furnace at a heating temperature of 450° C. for 3 hours at a heating rate of 5° C. / min to obtain a hard carbon-silicon oxide solid mixture after the reaction;
[0038] (7) The hard carbon-silicon dioxide solid mixture obtained in step (6) is ball-milled in a vacuum planetary ball mill with a vacuum degree of 80 Pa, a ball-milling speed of 450 r / min, and a ball-milling time of 8 hours to obtain a hard carbon-silicon dioxide composite lithium-ion battery negative electrode material.
[0039] Example 2
[0040] A method for preparing a hard carbon-silicon dioxide composite lithium ion battery negative electrode material comprises the following steps:
[0041] (1) 500 g of peanut shell biomass and a mixture of 150 g of sodium hydroxide and sodium carbonate were uniformly mixed in a conical mixer, the mass ratio of sodium carbonate to sodium hydroxide was 8:2, the mixer speed was 450 r / min, and the mixing time was 1 hour;
[0042] (2) 300 g of the mixed product obtained in step (1) was heated and carbonized in a tube furnace at a carbonization temperature of 1000° C. for 2 hours at a heating rate of 4° C. / min, a nitrogen atmosphere at a nitrogen flow rate of 200 mL / min, to obtain a biomass hard carbon-sodium silicate mixture;
[0043] (3) 100 g of the biomass hard carbon-sodium silicate mixture obtained in step (2) was placed in a beaker, 2000 ml of aqua regia was added, and the mixture was placed on a magnetic heating stirrer for reaction for 6 hours at a heating temperature of 300° C. and a stirring speed of 900 r / min to obtain a hard carbon-silicic acid sol mixture;
[0044] (4) The hard carbon-silicic acid sol mixture obtained in step (3) was allowed to stand for 10 minutes, the supernatant was poured out and 1 L of high-purity deionized water was added, and the mixture was stirred with a glass rod for 1 minute, and then allowed to stand for another 10 minutes. After repeated washing 8 times, the pH of the reaction product was 6.5, and washing was stopped to obtain a hard carbon-silicic acid sol mixture slurry;
[0045] (5) placing the hard carbon-silicic acid sol mixture slurry obtained in step (4) in a vacuum drying oven for drying at a vacuum pressure of 80 Pa, a drying temperature of 90° C., and a drying time of 7 hours to obtain a hard carbon-silicic acid solid mixture;
[0046] (6) heating the hard carbon-silicic acid solid mixture obtained in step (5) in a box-type resistance furnace at a heating temperature of 500° C. for 2.5 hours at a heating rate of 4° C. / min to obtain a hard carbon-silicon oxide solid mixture after the reaction;
[0047] (7) The hard carbon-silicon dioxide solid mixture obtained in step (6) is ball-milled in a vacuum planetary ball mill with a vacuum degree of 90 Pa, a ball-milling speed of 600 r / min, and a ball-milling time of 6 hours to obtain a hard carbon-silicon dioxide composite lithium-ion battery negative electrode material.
[0048] Comparative Example 1: A lithium-ion battery artificial graphite negative electrode material, sourced from Inner Mongolia Sanxin Industrial Co., Ltd., model: SP2-2.
[0049] Comparative Example 2: A hard carbon negative electrode material for lithium-ion batteries, sourced from Inner Mongolia Sanxin Industrial Co., Ltd., model: SHC-1.
[0050] Comparative Example 3: A silicon oxide negative electrode material for lithium-ion batteries, sourced from Shanghai Naio Nano Technology Co., Ltd.
[0051] Test example:
[0052] The hard carbon-silicon oxide composite lithium ion battery negative electrode materials prepared in Comparative Examples 1-3 and Examples 1 and 2 were tested for gram capacity, rate performance, and cycle performance, and the results are shown in Table 1. The battery assembly preparation process is: using metallic lithium as the negative electrode active material, the hard carbon-silicon oxide composite lithium ion battery negative electrode materials prepared in Examples 1 and 2 and the negative electrode materials of Comparative Examples 1-3 are used as positive electrode active materials to assemble into CR2430 button-type half-cells according to the following charge and discharge procedures for gram capacity, rate performance, and cycle performance tests. The test uses a CT2001A blue electric test system.
[0053] 1. Basic parameter settings for gram capacity charge and discharge test: 1. Stand for 2 hours; 2. 0.1C discharge, cut-off voltage 0.005V; 3. 0.05C discharge, cut-off voltage 0.005V; 4. Stand for 15 minutes; 5. 0.1C charge, cut-off voltage is 2.0V; 6. The gram capacity recorded at 0.1C charge is the gram capacity of the negative electrode material.
[0054] 2. Basic parameter settings for rate performance charge and discharge test: 1. Stand for 2 hours; 2. 0.1C discharge, cut-off voltage 0.005V; 3. 0.05C discharge, cut-off voltage 0.005V; 4. Stand for 15 minutes; 5. 0.1C charge, cut-off voltage 2.0V; 6. 1C discharge, cut-off voltage 0.005V, 0.9C discharge, cut-off voltage 0.005V, 0.8C discharge, cut-off voltage 0.005V, 0.7C discharge, cut-off voltage Pressure 0.005V, 0.6C discharge, cut-off voltage 0.005V, 0.5C discharge, cut-off voltage 0.005V, 0.4C discharge, cut-off voltage 0.005V, 0.3C discharge, cut-off voltage 0.005V, 0.2C discharge, cut-off 0.005V, 0.1C discharge, cut-off voltage 0.005V; 7. 1C charge, cut-off voltage 2V; 8. Record the ratio of 1C charging gram capacity and 0.1C charging gram capacity, which is the rate performance.
[0055] 3. Basic parameter settings for cycle performance charge and discharge test: 1. Stand for 2 hours; 2. 0.1C discharge, cut-off voltage 0.005V; 3. 0.05C discharge, cut-off voltage 0.005V; 4. Stand for 15 minutes; 5. 0.1C charge, cut-off voltage is 2.0V; 6. 1C discharge, cut-off voltage 0.005V, 0.9C discharge, cut-off voltage 0.005V, 0.8C discharge, cut-off voltage 0.005V, 0.7C discharge, cut-off voltage 0.005V, 0.6C Discharge, cut-off voltage 0.005V, 0.5C discharge, cut-off voltage 0.005V, 0.4C discharge, cut-off voltage 0.005V, 0.3C discharge, cut-off voltage 0.005V, 0.2C discharge, cut-off 0.005V, 0.1C discharge, cut-off voltage 0.005V; 7. 1C charge, cut-off voltage 2V; 8. Repeat steps 6 and 7, and record the number of cycles experienced when the 1C charging gram capacity is less than or equal to 90% of the 1C charging gram capacity in step 6, which is the cycle performance.
[0056] Table 1
[0057]
[0058] See Table 1. Figure 1 , Figure 2 Comparative Example 1 is a high-end artificial graphite negative electrode prepared using high-quality raw materials. Its gram capacity is close to the theoretical gram capacity limit of artificial graphite, 372 mAh / g. There is very limited room for further improvement and it is of little significance. Comparative Example 2 is a hard carbon negative electrode. Although its cycle performance and rate performance are higher than those of artificial graphite, its gram capacity is lower. Comparative Example 3 is a silicon oxide negative electrode. Although its gram capacity is relatively high, its cycle performance and rate performance are poor. Examples 1 and 2 are composite negative electrodes of hard carbon and silicon oxide, which have the advantages of both hard carbon and silicon oxide, so that its gram capacity is higher than that of artificial graphite negative electrode, while its cycle performance and rate performance are comparable to those of artificial graphite.
[0059] It should be understood that the above description of the preferred embodiment is relatively detailed and cannot be regarded as limiting the scope of patent protection of the present invention. Under the enlightenment of the present invention, ordinary technicians in this field can also make substitutions or modifications without departing from the scope of protection of the claims of the present invention, which all fall within the scope of protection of the present invention. The scope of protection requested for the present invention shall be based on the attached claims.
Claims
1. A method for preparing a hard carbon-silicon dioxide composite lithium ion battery negative electrode material, comprising the following steps: (1) mixing a silicate-containing biomass and an alkali metal compound uniformly and then heating and carbonizing the mixture to obtain a biomass hard carbon-sodium silicate mixture; the silicate-containing biomass is one of walnut shell biomass and peanut shell biomass; (2) adding aqua regia to the biomass hard carbon-sodium silicate mixture obtained in step (1) to react, dissolving the metal compound impurities in the biomass hard carbon into metal ions and converting the sodium silicate into silicic acid to obtain a hard carbon-silicic acid sol mixture; (3) washing and drying the hard carbon-silicic acid sol mixture obtained in step (2) to obtain a hard carbon-silicic acid solid mixture; (4) The hard carbon-silicic acid solid mixture obtained in step (3) is heated and then ball-milled to obtain a hard carbon-silicon dioxide composite lithium-ion battery negative electrode material.
2. The preparation method according to claim 1, characterized in that: The alkali metal compound in step (1) is one or a mixture of two of sodium hydroxide, sodium carbonate and sodium borate; the mass ratio of the biomass to the alkali metal compound in step (1) is 100:10-40.
3. The preparation method according to claim 1, characterized in that: The equipment used for mixing the biomass and the alkali metal compound in the step (1) is a cone mixer, the mixer speed is 300-500r / min, and the mixing time is 1-4 hours; the heating carbonization in the step (1) is carried out in a tubular furnace with a protective atmosphere, the carbonization temperature is 800-1200°C, the carbonization time is 2-4 hours, the heating rate is 2-10°C / minute, the protective atmosphere is nitrogen, and the nitrogen flow rate is 100-200mL / min.
4. The preparation method according to claim 1, characterized in that: The mass ratio of aqua regia to the biomass hard carbon-sodium silicate mixture in step (2) is 16-25:1; the reaction of aqua regia and the biomass hard carbon-sodium silicate mixture in step (2) is carried out on a magnetic heating stirrer, the heating temperature is 200-300°C, the reaction time is 4-8 hours, and the stirring speed is 600-1200r / min.
5. The preparation method according to claim 1, characterized in that: The washing process in step (3) is as follows: first, the reaction product in step (2) is allowed to stand and settle for 10-15 minutes, the supernatant is poured out and 1L of high-purity deionized water is added, and after stirring for 1 minute, the mixture is allowed to stand and settle for another 10-15 minutes. This washing process is repeated 5-10 times until the pH of the reaction product reaches between 6.5 and 7, and the washing is completed.
6. The preparation method according to claim 1, characterized in that: The drying in step (3) is carried out in a vacuum drying oven, the vacuum pressure is less than 100 Pa, the drying temperature is 80-120° C., and the drying time is 4-8 hours.
7. The preparation method according to claim 1, characterized in that: The heating reaction in step (4) is carried out in a box-type resistance furnace, the heating temperature is 400-600°C, the heating time is 2-4 hours, and the heating rate is 4-8°C / min.
8. The preparation method according to claim 1, characterized in that: The ball milling in step (4) is carried out in a planetary ball mill capable of evacuating vacuum, the vacuum degree is less than 100 Pa, the ball milling speed is 400-800 r / min, and the ball milling time is 6-12 hours.
9. A hard carbon-silicon dioxide composite lithium ion battery negative electrode material prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the hard carbon-silicon dioxide composite lithium ion battery negative electrode material according to claim 9 in the preparation of lithium ion batteries.
Citation Information
Patent Citations
Preparation of hard carbon negative electrode material for lithium ion power battery and modification method therefor
WO2017121069A1
Preparation method for silicon-carbon negative electrode material and use thereof
WO2023142675A1